2019
DOI: 10.1177/1534735419828829
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Moringa oleifera and Ionizing Radiation on Survival and Metastatic Activity of Pancreatic Cancer Cells

Abstract: Background: Radiotherapy is one of the main treatments for malignancies. Radioresistance is a major obstacle in this treatment, calling for new treatments to improve radiotherapy outcome. Herbal medicine has low toxicity and could be a source for new radio-enhancing agents. Moringa oleifera (moringa) is a well-known medicinal plant with antiproliferative and antimetastatic properties. Possible mechanisms of moringa anticancer activity may be related to the expression of PARP-1, Bcl-2, COX-2, p65, p-IκB-a, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Although it has been accepted widely, the chemoresistance is one of the major issues associated with this drug. Currently, studies on drug combination have been well recognized in the cancer research community, with the aim to reduce toxicity, minimize the induction of drug resistance, as well as to achieve additional therapeutic effect [5]. Thus, the focus had been drawn towards traditional herbal medicine, which could be an alternative approach to overcome the limitation of gemcitabine against pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been accepted widely, the chemoresistance is one of the major issues associated with this drug. Currently, studies on drug combination have been well recognized in the cancer research community, with the aim to reduce toxicity, minimize the induction of drug resistance, as well as to achieve additional therapeutic effect [5]. Thus, the focus had been drawn towards traditional herbal medicine, which could be an alternative approach to overcome the limitation of gemcitabine against pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It contains large amounts of various phytochemicals including phenolics, tannins, saponin, glucosinolates, flavonoids, flavonol glycosides, quercetin, kaempferol, phytate, and lectins (Maizuwo et al, 2017;Atta et al, 2017;. These phytochemicals help in treating various diseases as antidiarrheal, antiulcerative, and hepato-and nephroprotective, antidiabetic and anticancer effects (Gopalakrishnan et al, 2016;Shalaby et al, 2016;Atta et al, 2017Atta et al, , 2018Villarruel-López et al, 2018;Hagoel et al, 2019). All parts of MO tree are edible.…”
mentioning
confidence: 99%
“…Yet the disease has not been conquered and the development of new targeted therapy is still going on. Natural products are major sources providing due to their potentially low toxicity and potential effectiveness, but the functional mechanism of most of them remain unclear [ 41 , 42 ]. The present study showed that arctigenin reduced the expressions of tumor-derived GM-CSF and TSLP through NF-κB p65 to inhibit breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%